Pros and Cons of 19 Sport-Related Concussion Educational Resources in Canada: Avenues for Better Care and Prevention - Cusimano, Michael D.; Zhang, Stanley; Topolovec-Vranic, Jane; Grosso, Ashley; Jing, Rowan; Ilie, Gabriela (Frontiers in Neurology, 2018)
Objective: The goal of this research was to assess the effectiveness of available concussion educational resources in Canada, the means used to disseminate this knowledge and the impact of these educational resources on players' concussion prevention knowledge. Methods: We assessed concussion knowledge before and after exposure to one or more of 19 resources introduced through a national program aimed to increase awareness and knowledge of concussion. The effectiveness of the mode of delivery was measured by changes in concussion knowledge scores (CKS) between pre and pro scores. Measures: Concussion knowledge scores (CKS) were calculated for pre- and post- exposure to concussion educational resources and used as a measure of both, the effectiveness of each resource as well as the effectiveness of the delivery method. The effectiveness of each educational resource was also measured by the respondents' rating of each concussion educational resource. Results: Respondents in post-survey had higher CKS than those in pre-survey. Two out of the 19 newly developed concussion educational resources were effective in improving the resource users' CKS. Linear regression showed that using more resources further increased CKS. Four out of six modes of delivery enhanced respondents' concussion knowledge. Conclusion: Our findings demonstrate that the newly developed Canadian concussion educational resources were effective at improving users' concussion knowledge. Our data demonstrates that using three or more resources further enhanced the users' concussion knowledge. Future research, however, is critical to assess whether concussion prevention knowledge is sufficient to reduce injuries and factors influencing it.